2014
DOI: 10.1016/j.tine.2014.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and school education

Abstract: a b s t r a c tSleep has emerged in the past decades as a key process for memory consolidation and restructuring. Given the universality of sleep across cultures, the need to reduce educational inequality, the low implementation cost of a sleep-based pedagogy, and its global scalability, it is surprising that the potential of improved sleep as a means of enhancing school education has remained largely unexploited. Students of various socio-economic status often suffer from sleep deficits. In principle, the opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 103 publications
(124 reference statements)
0
24
1
Order By: Relevance
“…In a questionnaire study, sleep behavior (especially during the pre-exam period), together with the results in the pre-clinical board exam, turned out as the strongest predictor for the final grade in the medical exam (Genzel et al, 2013 ). Improving sleep in children and students might therefore be a promising target to improve school performance (Ribeiro and Stickgold, 2014 ).…”
Section: Optimizing Sleep's Beneficial Influence On Memorymentioning
confidence: 99%
“…In a questionnaire study, sleep behavior (especially during the pre-exam period), together with the results in the pre-clinical board exam, turned out as the strongest predictor for the final grade in the medical exam (Genzel et al, 2013 ). Improving sleep in children and students might therefore be a promising target to improve school performance (Ribeiro and Stickgold, 2014 ).…”
Section: Optimizing Sleep's Beneficial Influence On Memorymentioning
confidence: 99%
“…That being put, schools should provide strategies to improve students’ learning, such as after-shift naps, instructions for a good night’s sleep, and information about their benefits with a view to more efficient learning. 31 …”
Section: Discussionmentioning
confidence: 99%
“…A questionnaire study indicated that sleep behaviour turned out to be the strongest predictor for the final grade in the medical examination (Genzel et al, 2013). Accordingly, "Well-rested children do better at school" might not be a myth at all, and improving sleep in children and students might be a promising target to improve school performance (Ribeiro & Stickgold, 2014). instead, it is an active state.…”
Section: How Much Sleep Is Needed?mentioning
confidence: 99%